It better be good, it better be green - Fabio Fornari; Daniele Pianeselli; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
We provide empirical evidence that the pricing of green bonds tends to be highly sophisticated and based on a two-tiered approach. When buying a green bond, investors do not look only at the green label of the bond but also consider additional characteristics that involve the soundness of the underlying project and the environmental score of the issuer. By comparing the yields at issuance of green bonds to those of a matched control sample of conventional bonds, we identify a premium of 16 basis points for the green label alone. However, when the environmental score of the issuer is in the top tercile of the cross-sectional distribution, the greenium increases up to doubling. Green certification and periods of heightened climate uncertainty also significantly influence the size of the greenium. Additionally, we find that this pricing mechanism fully emerged only after the Paris Agreement came into force in late 2016.
Keywords: 330